Hypomethylation of TET2 Target Genes Identifies a Curable Subset of Acute Myeloid Leukemia - Yamazaki, Jumpei (J Natl Cancer Inst, 2015)
BACKGROUND: Acute myeloid leukemia (AML) is curable in a subset of cases. The DNA methylation regulator TET2 is frequently mutated in AML, and we hypothesized that studying TET2-specific differentially methylated CpGs (tet2-DMCs) improves AML classification. METHODS: We used bisulfite pyrosequencing to analyze the methylation status of four tet2-DMCs (SP140, MCCC1, EHMT1, and MTSS1) in a test group of 94 consecutive patients and a validation group of 92 consecutive patients treated with cytarabine-based chemotherapy. Data were analyzed with hierarchical clustering, Cox proportional hazards regression, and Kaplan-Meier analyses. All statistical tests were two-sided. RESULTS: In the test cohort, hierarchical clustering analysis identified low levels of tet2-DMC methylation in 31 of 94 (33%) cases, and these had markedly longer overall survival (median survival 72+ vs 14 months, P = .002). Similar results were seen in the validation cohort. tet2-DMC–low status was shown to be an independent predictor of overall survival (hazard ratio = 0.29, P = .0002). In The Cancer Genome Atlas (TCGA) dataset where DNA methylation was analyzed by a different platform, tet2-DMC–low methylation was also associated with improved outcome (median survival = 55 vs 15 months, P = .0003) and was a better predictor of survival than mutations in TET2, IDH1, or IDH2, individually or combined. CONCLUSIONS: Low levels of tet2-DMC methylation define a subgroup of AML that is highly curable and cannot be identified solely by genetic and cytogenetic analyses.